Time-varying World Integration of the Malaysian Stock Market: A Kalman Filter Approach - Bit-Kun Yeoh,; Chee-Wooi Hooy,; Zainudin Arsad, (Asian Academy of Management Journal of Accounting and Finance, 2010)
This paper estimates the time-varying world integration of the Malaysian stock market and examines if the paths of the time-varying integration match the economic events of the country. We employed weekly time series data for the period between February 1988 and September 2009 to coincide with the liberalisation of the Malaysian market since the late 1980s. To capture the time-varying degree of market integration, we employed the Kalman Filter technique, which produces time-varying coefficients in estimating International Capital Asset Pricing Model (ICAPM). The changes in the level of market integration coincide with the economic events that took place in the country and provide some evidence to the practical application and suitability of the Kalman Filter technique in studying stock market integration.